2021
DOI: 10.1111/ijal.12333
|View full text |Cite
|
Sign up to set email alerts
|

Differences in emotional reactions of Greek, Hungarian, and British users of English when watching television in English

Abstract: We investigated differences in self‐reported Emotional Reactions (ER) of first (L1) and foreign (LX) language users of English when watching television in English and identified the predictors. Participants were 271 British citizens, 282 Greek, and 271 Hungarians living in their home country. English LX users had significantly lower values for ER compared to L1 users. Frequency of watching television in English and Trait Emotional Intelligence were the strongest predictors of ER among LX users. No significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Multilinguals' languages may also "feel" different because of variation in levels of emotional resonance: LXs typically have less emotional power than first languages (L1s), and LXs are typically dispreferred for communicating emotions (Dewaele, 2013). Even films and news bulletins in the LX have been found to elicit weaker emotional reactions among LX users compared to L1 users (Dewaele, Lorette, Rolland & Mavrou, 2021). The authors discovered that 553 English LX users reported lower frequency of feeling emotional when watching the news or a film, lower frequency of laughter when watching a funny film, and a lower degree of trust in news reports in English compared to 271 L1 users.…”
Section: Communicating Emotions In Multiple Languagesmentioning
confidence: 99%
“…Multilinguals' languages may also "feel" different because of variation in levels of emotional resonance: LXs typically have less emotional power than first languages (L1s), and LXs are typically dispreferred for communicating emotions (Dewaele, 2013). Even films and news bulletins in the LX have been found to elicit weaker emotional reactions among LX users compared to L1 users (Dewaele, Lorette, Rolland & Mavrou, 2021). The authors discovered that 553 English LX users reported lower frequency of feeling emotional when watching the news or a film, lower frequency of laughter when watching a funny film, and a lower degree of trust in news reports in English compared to 271 L1 users.…”
Section: Communicating Emotions In Multiple Languagesmentioning
confidence: 99%
“…Both the process of conceptual development and affective linguistic conditioning contribute to language embodiment, in which words trigger both sensory images and physiological reactions. Findings from cognitive psychologists and multilingualism researchers using a wide range of epistemological and methodological approaches suggest that the L1 of multilinguals is typically felt as more emotional, authentic and potent compared to LXs and that physiological reaction to emotion words is stronger in the L1 (Dewaele, 2013;Dewaele et al, 2021;Caldwell-Harris, 2015;Pavlenko, 2005Pavlenko, , 2012. Pavlenko (2012, p. 409) defined affective processing as the 'somatovisceral responses triggered by automatic appraisal of verbal stimuli, which may or may not register as subjective feelings at the level of higher cognition'.…”
Section: Emotions In Multiple Languagesmentioning
confidence: 99%
“…The LX, acquired later in life, allowed them to 'feel "protected" by the linguistic detachment' (p. 558) it offered. Further evidence of this 'emotional-detachment effect' has emerged in the broader areas of psychology and multilingualism research (Dewaele, 2013(Dewaele, , 2021Caldwell-Harris, 2015). Surprisingly, however, many psychotherapists remain unaware of the role of strategic code-switching among multilingual clients (Costa & Dewaele, 2019;Rolland, Costa & Dewaele, 2021;Rolland, Dewaele & Costa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different methodological approaches have been followed in the attempt to answer that question: i) introspective studies that assess bilinguals' perception of emotionality in their respective languages (e.g., Dewaele, 2004Dewaele, , 2008Dewaele, Lorette, Rolland & Mavrou, 2021); ii) cognitively oriented studies where the effects of the emotional content of words (defined in relation to the dimensions of valence-ranging from pleasant to unpleasant, and arousalranging from exciting to calming) in the two languages is examined with different experimental paradigms, such as the lexical decision task (e.g., Ferré, Anglada-Tort & Guasch, 2018;Ponari, Rodríguez-Cuadrado, Vinson, Fox, Costa & Vigliocco, 2015), the emotional Stroop task (e.g., Eilola & Havelka, 2011;Sutton, Altarriba, Gianico & Basnight-Brown, 2007), the affective priming paradigm (e.g., Degner, Doycheva & Wentura, 2012) or memory tasks (e.g., Ayçiçeği-Dinn & Caldwell-Harris, 2009;Ferré, García, Fraga, Sánchez-Casas & Molero, 2010); iii) psychophysiological studies, where physiological markers of arousal (mostly the skin conductance response, SCR) are recorded when words that differ in emotional content (including, for instance, swearwords or taboo words) are presented in L1 and L2 (e.g., Baumeister, Foroni, Conrad, Rumiati & Winkielman, 2017;Caldwell-Harris, Tong, Lung & Poo, 2011;Eilola & Havelka, 2011; see also Iacozza, Costa &Duñabeitia, 2017 andToivo &Scheepers, 2019, for studies recording the pupillary response); iv) and electrophysiological and neuroimaging studies, where the time course of emotional processing is recorded (e.g., Conrad, Recio & Jacobs, 2011;Jończyk, Boutonnet, Musiał, Hoemann & Thierry, 2016;Wu & Thierry, 2012), or the neural areas involved in such processing are identified (e.g., Hsu, Jacobs & Conrad, 2015) while bilingual speakers are presented with L1 and L2 words.…”
Section: Introductionmentioning
confidence: 99%